KAMPUNG ADAT TAKPALA: STUDI PEMBERDAYAAN MASYARAKAT LOKAL DALAM PENGEMBANGAN PARIWISATA BERBASIS KOMUNITAS - Kolly, Onun Asnat Waang; Aryaningtyas, Aurilia Triani (STABN Raden Wijaya Wonogiri, 2025)
The Traditional Adat Village of Takpala in Alor Regency, East Nusa Tenggara, is a cultural destination with significant potential to be developed as a community-based tourism (CBT) village. The authenticity of its traditional houses, preserved social structures, and rich cultural heritage make the village appealing to tourists. This study aims to examine the forms and processes of local community empowerment in tourism development in Takpala Village through the CBT approach. The research employs a descriptive qualitative method, with data collection techniques including observation, in-depth interviews, and documentation. The informants consist of traditional leaders, local tourism actors, village government officials, and representatives of the general community. The findings indicate that community involvement in tourism development is evident through tour guiding, cultural performances, and visitor management activities. However, challenges remain in areas such as human resource training, marketing, and the sustainability of tourism initiatives. This study recommends strengthening collaboration among stakeholders and enhancing local capacities to support inclusive, sustainable, and culturally grounded tourism development.